2017
DOI: 10.1542/peds.2016-2883
|View full text |Cite
|
Sign up to set email alerts
|

The Concordance of Parent and Child Immunization

Abstract: BACKGROUND: A substantial body of work has related survey-based parental vaccine hesitancy to noncompliant childhood immunization. However little attention has been paid to the connection between parents' own immunization behavior and the immunizations their children receive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
0
17
1
Order By: Relevance
“…One study revealed that children were 2.77 times (95% CI 2.74 to 2.79) more likely to also be immunized for seasonal influenza if their parents were immunized. 8 When parents who were previously not immunized had received immunization for seasonal influenza, their children were 5.44 times (95% CI 5.35 to 5.53) more likely to receive an influenza vaccine.…”
Section: The 2017-2018 Influenza Season Was a High-severity Season Wmentioning
confidence: 99%
See 1 more Smart Citation
“…One study revealed that children were 2.77 times (95% CI 2.74 to 2.79) more likely to also be immunized for seasonal influenza if their parents were immunized. 8 When parents who were previously not immunized had received immunization for seasonal influenza, their children were 5.44 times (95% CI 5.35 to 5.53) more likely to receive an influenza vaccine.…”
Section: The 2017-2018 Influenza Season Was a High-severity Season Wmentioning
confidence: 99%
“…The vaccination of health care workers is a crucial step in preventing influenza and reducing health care-associated influenza infections because health care personnel often care for individuals at high risk for influenza-related complications. 8. Pediatricians should attempt to promptly identify their patients who are suspected of having an influenza infection for timely initiation of antiviral treatment when indicated and on the basis of shared decision-making between each pediatrician and child caregiver to reduce morbidity and mortality.…”
Section: The 2017-2018 Influenza Season Was a High-severity Season Wmentioning
confidence: 99%
“…1,48 Substantial evidence has accumulated regarding the efficacy of maternal influenza immunization in preventing laboratory-confirmed influenza disease and its complications in both mothers and their infants in the first 2 to 6 months of life. [48][49][50][51][52][53] Pregnant women who are immunized against influenza at any time during their pregnancy provide protection to their infants during their first 6 months of life, when they are too young to receive influenza vaccine themselves, through transplacental passage of antibodies. [50][51][52][53][54][55][56][57][58] Infants born to women who receive influenza vaccination during pregnancy can have a risk reduction of up to 72% (95% CI, 39% to 87%) for laboratory-confirmed influenza hospitalization in the first few months of life.…”
Section: Influenza Vaccines During Pregnancy and Breastfeedingmentioning
confidence: 99%
“…[59][60][61][62][63] Authors of 1 study found that children were 2.77 times (95% CI, 2.74 to 2.79) more likely to be immunized against seasonal influenza if their parents were immunized. 33 When parents who were previously not immunized had received immunization for seasonal influenza, their children were 5.44 times (95% CI, 5.35 to 5.53) more likely to receive influenza vaccine.…”
Section: Influenza Vaccine Coveragementioning
confidence: 99%
“…1,32 Substantial evidence has accumulated regarding the efficacy of maternal influenza immunization in preventing laboratory-confirmed influenza disease and its complications in both mothers and their infants in the first 2 to 6 months of life. 14,[32][33][34][35][36][37] Pregnant women who are immunized against influenza at any time during their pregnancy provide protection to their infants during their first 6 months of life (when they are too young to receive influenza vaccine themselves) through transplacental passage of antibodies. 38,39 Infants born to women who receive influenza vaccination during pregnancy can have a risk reduction of 72% (95% CI, 39% to 87%) for laboratoryconfirmed influenza hospitalization in the first few months of life.…”
Section: Influenza Vaccines During Pregnancy and Breastfeedingmentioning
confidence: 99%